Use of cardiac magnetic resonance to detect changes in metabolism in heart failure - Watson, WD; Miller, JJJ; Lewis, A; Neubauer, S; Tyler, D; Rider, OJ; Valkovič, L (AME Publishing Company, 2020)
The heart has a massive adenosine triphosphate (ATP) requirement, produced from the oxidation of metabolic substrates such as fat and glucose. Magnetic resonance spectroscopy offers a unique opportunity to probe this biochemistry: 31Phosphorus spectroscopy can demonstrate the production of ATP and quantify levels of the transport molecule phosphocreatine while 13Carbon spectroscopy can demonstrate the metabolic fates of glucose in real time. These techniques allow the metabolic deficits in heart failure to be interrogated and can be a potential future clinical tool.